Efficacy of Diode Laser With Different Intensities as an Adjunct to Traditional Mechanical Treatment of Chronic Periodontitis (Mustansiria Dental Journal, 2018)
The recent decades, considerable attention has focused on using of different typesof laser irradiation in treatment of periodontal diseases. The aim of the present studywas the assessment of efficacy of low-level and high-level diode laser treatment incombination with scaling and root planing (SRP) in patients with chronicperiodontitis. The total sample of the present study consisted of twelve patients hadmoderate to severe chronic periodontitis in at least (3) vital single-rooted teeth indifferent quadrants of each patient.These teeth of the twelve patients were allocated into three groups according to thetype of the received treatment (12 teeth from 12 patients for each group).1- Group A (GA) treated with scaling & root planing ( SRP).2- Group B (GB) (SRP + low-level laser).3- Group C (GC) (SRP + high-level laser).Clinical measurements were performed by a single well trained and calibratedexaminer, and they included, plaque index (PI), gingival index (GI), bleeding onprobing (BOP), clinical attachment level (CAL) and probing pocket depth (PPD). Theresults of the present study were positive and predictable in both lasers irradiationmodes. The differences between the changes of the SRP group (GA), and two laserslow and high density lasers combined with SRP groups (GB & GC) at baseline werenot significant. All of the clinical parameters that were investigated in this study haveshowed a significant improvement at 6 months from the baseline for the three groupsof the study. These findings reported that low & high-level diode laser can have abeneficial effect in treatment of chronic periodontitis in combination with traditionalmechanical treatment